Recent Advances in Arc-linear Motors for Direct-drive Applications: A Review - Zhenbao Pan; Jiwen Zhao; Shuhua Fang; Jinhao Cai; Qiangren Xu (CES Transactions on Electrical Machines and Systems, 2025)
The arc-linear motor (ALM) is a new type of special motor derived from the linear motor, which has the merits of high torque, compact structure and fast dynamic response. This kind of motor does not need a complex intermediate transmission device, it is used in some direct-drive applications for continuous rotation or limited angle motion. However, there is no systematic summary and generalization of the ALMs so far. Therefore, this paper systematically overviews the recent advances in ALMs for direct-drive systems. First, the evolution process and basic structure of the ALM are introduced. And then, various ALMs are reviewed with particular reference to motor topologies, working principle, motor performance, optimization design and control techniques. To heel, a comprehensive comparison of several typical ALMs is carried out. Finally, the application areas, main challenges and development trends of the ALMs are highlighted.